Characteristics and patterns of sweetener use in ultra-processed food products available in Brazilian supermarkets - Daniela Silva Canella; Maria Emília Coimbra Pereira; Mariana Ribeiro; Maria Eduarda Ribeiro José; Laís Amaral Mais; Ana Paula Bortoletto Martins (Scientific Reports, 2026)
Abstract Sweeteners are non-sugar food additives that provide a sweet taste to products and, according to the Nova Classification, they are markers of ultra-processing. This study aimed to characterize the use of sweeteners in ultra-processed food products available for consumption in Brazil, pre-labeling-reform. Based on data from about 10,000 packaged products with lists of ingredients collected in Brazilian supermarkets in 2017, this study identified 910 products (9.2%) whose list of ingredients included sweeteners. The distribution of the number and types of sweeteners in the products was analyzed, and factor analysis was performed to identify the patterns of sweetener use. Sweeteners were used in products such as non-carbonated beverages, sweets in general, and sweetened dairy beverages; sucralose was the most prevalent sweetener (53%), followed by acesulfame potassium (50%) and sodium cyclamate (33%). These additives were mostly used together; that is, several products contained a combination of two or more types of sweeteners, and there were products that alone were formulated with four or more sweeteners. Factor analysis identified four different patterns of additive use, and sweet cookies, tabletop sweeteners, and cakes and sweet pies were the subgroups that stood out when associated with the patterns of sweeteners use.